Social and Cultural Aspects in Harry Potter Sorcerer’s Stone - Purba, Nurhayati; Silalahi, Rachael Joy Nabasa; Napitupulu, Cindy Ardauli Togiana; Ersan, Ronaldo (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This article examines the social and cultural aspects shown in Harry Potter and the Sorcerer's Stone by J.K. Rowling. Beyond its fantasy narrative, the novel portrays real-world social issues such as family dynamics, bullying, personal identity, social class, and cultural prejudice within both the magical and non-magical worlds. Through a qualitative approach using library research, this study identifies how social environments, peer interactions, institutional influences, and cultural norms shape character development, particularly that of the protagonist, Harry Potter. The analysis highlights how the novel reflects British cultural heritage, including the class system, educational structures, and traditions, as well as issues of discrimination based on blood status. This study contributes to understanding how popular literature serves as a medium for representing and critiquing social and cultural realities.